ANALISA DAMPAK LALU LINTAS JEMBATAN MUSI VI KOTA PALEMBANG (Universitas Muhammadiyah Palembang, 2022)
Traffic impact analysis is one of the studies used to identify traffic impacts due to land use changes that result in the emergence of travel rise and pulls that will affect traffic performance on road sections. The purpose of traffic impact analysis Musi VI Bridge is to analyze the existing traffic conditions in the road network affected by the construction of the Musi VI Bridge, analyze the impact of the construction of the Musi VI Bridge, analyze the performance of the intersection. In the area opposite the Sultan Mansyur road towards Bukit Besar, at this time the process of proposing detail engineering desain widening the road. On the opposite side of the ulu road Faqih Usman - access road to road KH. Wahid Hasyim carried out further work and will be opened to the public.